Assessing the influence of supply chain collaboration value innovation, supply chain capability and competitive advantage in Taiwan's networking communication industry - Liao, Shu-Hsien; Hu, Da-Chian; Ding, Li-Wen (International journal of production economics, 2017)
Taiwan's networking communication industry has had a clustering scale and a good position for collaboration in the global networking communication manufacturing network. This study considers whether Taiwan's networking communication industry can enhance its competitive advantage through supply chain management activities. In order to examine the relationships of supply chain collaboration value innovation, supply chain capability and competitive advantage, this research selects 74 firms and 465 questionnaires from the upstream, middle and downstream manufactures of Taiwan networking communication industry for research subjects, and uses structural equation modeling (SEM) to verify the theoretical model. Results show that the relationships among supply chain collaboration value innovation, supply chain capacity and competitive advantage can have a positive impact, and that supply chain capability is a full mediator. Moreover, supply chain echelons (upper, middle and downstream) have some moderating effects in these relationships. [Display omitted] •Taiwan's networking communication industry has a good position for collaboration in the global manufacturing network.•This study uses structural equation modeling (SEM) to verify the theoretical model.•Results show that the relationships among SCCVI, SCC and CA can have a positive impact.•Supply chain capability is a full mediator.•Moreover, supply chain echelons have some moderating effects in these relationships.